Genome-wide DNA methylation levels and altered cortisol stress reactivity following childhood trauma in humans - Lotte C. Houtepen; Christiaan H. Vinkers; Tania Carrillo-Roa; Marieke Hiemstra; Pol A. van Lier; Wim Meeus; Susan Branje; Christine M. Heim; Charles B. Nemeroff; Jonathan Mill; Leonard C. Schalkwyk; Menno P. Creyghton; et al. (Nature Communications, 2016)
Exposure to childhood trauma is a major risk factor for the development of almost all psychiatric disorders. By epigenome-wide studies, here, Houtepen et al. show that DNA methylation at a locus in the Kit ligand gene (KITLG) mediates the relationship between childhood trauma and cortisol stress reactivity.